A method for preparing a high molecular polymer with segmented distribution of sulfur cadmium zinc quantum dots

Through the super molecular aggregation design, the composite is assembled by the mackeole derivatives and the cadmium -sulfur zinc quantum dot to form a polymer polymer distributed in segmented sulfur, cadm, zinc quantum dot, The problem of cleansing treatment of benzene ether has achieved efficient degradation and environmental friendly material performance.

CN118930886BActive Publication Date: 2025-01-28JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411090750.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-01-28
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The polymers obtained by the traditional polymerization method are not easy to be further processed due to the irreversibility of covalent polymerization, which limits the application of polymer materials in various fields. At the same time, decabromodiphenyl ether is difficult to dissolve in solvents as a carcinogen and flame retardant, making it difficult to clean and process it.

Method used

Through the super molecular aggregation design, the composite is assembled by the mackeole derivatives and the cadmium -sulfur zinc quantum dots to form a polymer polymer distributed in segments distributed by sulfur, cadm, zinc, and quantum dots. After the PDI super molecular aggregation, the in -situ sulfur cadm and cadmium zinc quantum dot is formed to form a segment self -assembly body, which improves the degradation performance and stability of the material.

Benefits of technology

The high strength of the polymer polymer is not easy to destroy, high temperature resistance, small environmental impact, stable light, and excellent degradation performance to ten bromine phenyl ether, and there is no additional by -products, which is friendly to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930886B_ABST
    Figure CN118930886B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material preparation, and discloses a method for preparing a high molecular polymer with segmented distribution of zinc cadmium sulfur quantum dots. The method for preparing the high molecular polymer with segmented distribution of zinc cadmium sulfur quantum dots comprises the following steps: S1: mixing perylenetetracarboxylic dianhydride, dodecylamine and imidazole to react to obtain a perylene diimide derivative; S2: mixing sulfur powder, octadecene, cadmium oxide, zinc acetate and oleylamine to react to obtain zinc cadmium sulfur quantum dots; S3: assembling and compounding the perylene diimide derivative and the zinc cadmium sulfur quantum dots to obtain the high molecular polymer with segmented distribution of zinc cadmium sulfur quantum dots. The obtained high molecular polymer with segmented distribution of zinc cadmium sulfur quantum dots effectively improves the effect of degrading decabromodiphenyl ether.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation and discloses a method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots. Background Art

[0002] The polymers obtained by traditional polymerization methods are small molecule monomers that form macromolecular aggregates through irreversible covalent polymerization, i.e. covalent polymerization. Although the polymers obtained by this method have good mechanical properties, the polymer materials are not easy to further process due to the irreversibility of covalent polymerization, which limits the application of polymer materials in various fields. In contrast, supramolecular polymerization is a synthetic method based on supramolecular chemistry principles, which realizes the synthesis of supramolecular ordered polymers through non-covalent interactions between molecules. The dynamic reversibility of these non-covalent bonds gives supramolecular polymers special properties, such as stimulus responsiveness, self-healing, and self-adaptation. This technology has brought revolutionary changes to modern chemistry and materials science, especially in the fields of biomedicine, materials science, sensing and nanotechnology.

[0003] Zinc cadmium sulfate quantum dots (ZnCdS QDs) are a kind of nanomaterials with special optoelectronic properties. Quantum dots with a size of about 5nm can be prepared by hot injection. Zinc cadmium sulfate quantum dots have excellent optical properties, such as high luminescence efficiency, adjustable luminescence wavelength, and long fluorescence lifetime. They are widely used in fluorescent probes, optoelectronic devices, biomedicine, and photocatalysis. Therefore, zinc cadmium sulfate quantum dots have broad development prospects and great scientific research value.

[0004] Perylene diimide (PDI) has attracted the interest of many researchers due to its unique rigid conjugated plane, excellent chemical and photophysical stability, good electron acceptor performance, modifiability and strong absorption in the visible light region. It is one of the important materials for supramolecular polymerization self-assembly of organic polymer materials and is widely used in fluorescent chemical sensors, organic semiconductor materials, solar cells and other fields. The general rule for the design of PDI side chains is to minimize steric hindrance to promote molecular stacking. For this reason, linearly configured side chains are usually used for 1D self-assembly. PDI self-assembly methods with different morphologies and functions have undergone a lot of research, but the in-situ composite of sulfur cadmium zinc quantum dots onto the assembled PDI and PDI polymers with obvious segmentation have not been reported.

[0005] Decabromodiphenyl ether is an organic compound, a broad-spectrum, high-efficiency, additive flame retardant, with the characteristics of small addition amount, strong flame retardancy and high thermal stability, and is widely used in rubber, textile, electronics, plastic and other industries. Decabromodiphenyl ether is a carcinogen with acute toxicity, tumorigenicity and reproductive toxicity. When decabromodiphenyl ether is used in production, enterprises should clean it. However, decabromodiphenyl ether is almost insoluble in all solvents. Therefore, the present invention provides a method for preparing a high-molecular polymer with segmented distribution of sulfur cadmium zinc quantum dots. The self-assembly body has high strength and is not easy to be destroyed, is resistant to high temperature, is less affected by the environment, is more stable when illuminated, and is highly controllable. It greatly optimizes the performance of degrading decabromodiphenyl ether, and no additional by-products are produced. It is environmentally friendly and does not pollute the environment. The preparation process is relatively simple and easy to operate. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a high molecular polymer with segmented distribution of cadmium zinc sulfur quantum dots, and to design a segmented PDI supramolecular polymer with excellent degradation ability for decabromodiphenyl ether through supramolecular polymerization.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots comprises the following steps:

[0009] S1: mixing perylenetetracarboxylic dianhydride, dodecylamine and imidazole to react to obtain a perylene diimide derivative;

[0010] S2: mixing sulfur powder, octadecene, cadmium oxide, zinc acetate and oleylamine to react to obtain sulfur-cadmium-zinc quantum dots;

[0011] S3: Assembling and compounding the perylene diimide derivative and the cadmium zinc sulfide quantum dots to obtain a high molecular polymer in which the cadmium zinc sulfide quantum dots are distributed in sections.

[0012] More optimally, in step S3, the assembling and compounding of the perylene diimide derivative and the cadmium zinc sulfide quantum dots comprises dissolving the perylene diimide derivative in a first solvent, and the ratio of the perylene diimide derivative to the first solvent is (5-15) mg / 100 ml.

[0013] More preferably, in step S3, the temperature of the assembly is 25-35°C.

[0014] More optimally, in step S3, the assembly and compounding comprises adding a second solvent to the perylene diimide derivative dissolved in the first solvent for heating and evaporation, and when the system reaches saturation, simultaneously adding the sulfur cadmium zinc quantum dots for assembly and compounding.

[0015] More optimally, in step S3, the time for the assembly is greater than or equal to 5 hours.

[0016] More optimally, when the volume of the perylene diimide derivative to which the second solvent is added is reduced by 4 / 5 upon heating and evaporation, the sulfur cadmium zinc quantum dots are added.

[0017] More optimally, the preparation of the perylene diimide derivative comprises the following steps: mixing perylene tetracarboxylic dianhydride, dodecylamine and imidazole and calcining the mixture to obtain a solid;

[0018] The solid is dispersed and centrifugally dried to obtain the perylene diimide derivative.

[0019] More optimally, the preparation of the sulfur-cadmium-zinc quantum dots comprises: heating and dissolving sulfur powder and octadecene to obtain a precursor;

[0020] Mixing cadmium oxide, zinc acetate, octadecene and oleylamine, heating and dissolving them, and then mixing them into the precursor to react to obtain a reactant;

[0021] The reactants are centrifuged to remove impurities and then dispersed in a first solvent at low temperature.

[0022] More optimally, the first solvent includes chloroform solvent, and the second solvent includes ethanol.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: (1) Since the oily sulfur-cadmium zinc quantum dots are in-situ segmentedly compounded onto the PDI monomer during the self-assembly process of dodecyl PDI, compared with compounding after the PDI supramolecular polymerization, the obtained oily sulfur-cadmium zinc quantum dots induce the segmented self-assembly of the PDI monomer in the solvent system, which has high strength, is not easy to be destroyed, is resistant to high temperature, is less affected by the environment, and is more stable when exposed to light, thereby greatly optimizing its performance in degrading decabromodiphenyl ether;

[0024] (2) The present invention adopts a supramolecular polymerization method combined with a non-covalent prepolymerization system, generates no additional by-products, is environmentally friendly, does not pollute the environment, and has a relatively simple preparation process and is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A high-angle annular dark-field scanning transmission electron microscope and elemental mapping diagram of the one-dimensional PDI nanorods after self-assembly in Example 1;

[0026] Figure 2 (a)-(c) high-resolution transmission electron microscopy and (d)-(g) transmission electron microscopy images of the one-dimensional segmented nano-PDI rods in Example 1;

[0027] Figure 3The debromination result of decabrominated diphenyl ether by the segmented zinc cadmium sulfur quantum dot PDI sample of Example 1;

[0028] Figure 4 This is the electron microscope image of the uneven segmented PDI assembled for 3 hours in comparative example 1;

[0029] Figure 5 Electron microscopic images of the inhomogeneous segmented perylene diimide assembled in Comparative Examples 2-4 at 10° C., 20° C. and 40° C., respectively;

[0030] Figure 6 This is an electron microscope image of perylene diimide nanorods in comparative example 5, which were partially assembled and then quantum dots were added to continue the assembly. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1:

[0033] S1: Preparation of perylene diimide derivatives

[0034] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder, which was PDI powder with dodecyl as the side chain. Finally, 5 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor.

[0035] S2: Preparation of CdZnS quantum dots

[0036] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0037] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0038] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat at 65℃ on a hot plate for 8h. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL, add 100μL of oily sulfur cadmium zinc quantum dot solution, and slowly cool at 25℃ to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 5h of self-assembly, centrifuge, store the resulting assembly in a certain amount of ethanol solvent, quench, and terminate its supramolecular polymerization reaction.

[0039] Embodiment 2:

[0040] S1: Preparation of perylene diimide derivatives

[0041] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder, which was PDI powder with dodecyl as the side chain. Finally, 10 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor.

[0042] S2: Preparation of CdZnS quantum dots

[0043] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2 The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0044] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0045] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat at 65℃ on a hot plate for 8h. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL, add 100μL of oily sulfur cadmium zinc quantum dot solution, and slowly cool at 25℃ to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 5h of self-assembly, centrifuge, store the resulting assembly in a certain amount of ethanol solvent, quench, and terminate its supramolecular polymerization reaction.

[0046] Embodiment 3:

[0047] S1: Preparation of perylene diimide derivatives

[0048] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder, which was PDI powder with dodecyl as the side chain. Finally, 15 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor.

[0049] S2: Preparation of CdZnS quantum dots

[0050] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2 The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0051] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0052] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat at 65℃ for 8h on a hot plate. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL, add 100μL of oily sulfur cadmium zinc quantum dot solution, and slowly cool at 35℃ to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 5h of self-assembly, centrifuge and store the resulting assembly in a certain amount of ethanol solvent for quenching to terminate its supramolecular polymerization reaction.

[0053] Comparative Example 1:

[0054] S1: Preparation of perylene diimide derivatives

[0055] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder, which was PDI powder with dodecyl as the side chain. Finally, 10 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor.

[0056] S2: Preparation of CdZnS quantum dots

[0057] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2 The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0058] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0059] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat it on a hot plate at 65°C. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL, add 100μL of oily sulfur cadmium zinc quantum dot solution, and slowly cool it at 25°C to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 3h of self-assembly, centrifuge, store the resulting assembly in a certain amount of ethanol solvent, quench it, and terminate its supramolecular polymerization reaction.

[0060] Comparative Example 2:

[0061] S1: Preparation of perylene diimide derivatives

[0062] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder, which was PDI powder with dodecyl as the side chain. Finally, 10 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor.

[0063] S2: Preparation of CdZnS quantum dots

[0064] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2 The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0065] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0066] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat it on a hot plate at 65°C. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL, add 100μL of oily sulfur cadmium zinc quantum dot solution, and slowly cool it at 10°C to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 5h of self-assembly, centrifuge, store the resulting assembly in a certain amount of ethanol solvent, quench it, and terminate its supramolecular polymerization reaction.

[0067] Comparative Example 3: The process of Comparative Example 3 is similar to that of Comparative Example 2, and the slow cooling temperature in step S3 is 20°C.

[0068] Comparative Example 4: The process of Comparative Example 3 is similar to that of Comparative Example 2, and the slow cooling temperature in step S3 is 40°C.

[0069] Comparative Example 5:

[0070] S1: Preparation of perylene diimide derivatives

[0071] 800 mg of perylenetetracarboxylic dianhydride (PTCDA), 4 g of dodecylamine, and 40 g of imidazole were ground evenly, and then calcined at 130°C for 5 h after nitrogen was passed through a tube furnace for 30 min. The obtained solid was dispersed in 100 mL of ethanol and 100 mL of 4M HCl solution and stirred for 12 h. Then, it was centrifuged several times with deionized water, and the obtained product was dried at 60°C in a vacuum drying oven. Finally, the red powder obtained by grinding was PDI powder. Finally, 10 mg of PDI powder was dissolved in 100 mL of chloroform solvent (first solvent) to obtain PDI mother liquor. The PDI powder was PDI powder with dodecyl as the side chain.

[0072] S2: Preparation of CdZnS quantum dots

[0073] 0.51 g sulfur powder and 16 mL octadecene were placed in a 100 mL three-necked flask under N 2 The precursor solution was heated to 150°C under N atmosphere until dissolved and stored at 80°C. 0.256 g of cadmium oxide, 0.368 g of zinc acetate, 13 mL of octadecene and 6 mL of oleic acid were placed in a 250 mL three-necked flask. 2 The mixture was heated to 300°C in an atmosphere and maintained for a certain period of time until dissolved, and 4 mL of the precursor solution was quickly injected. After reacting for 10 minutes, the mixture was cooled to 50°C. The mixture was centrifuged to remove impurities, and the sulfur cadmium zinc quantum dots were dispersed in a chloroform solution and stored at low temperature. The concentration of the dispersed quantum dots was 16.5 mg / ml.

[0074] S3: Assembling composite polymers with segmented distribution of sulfur-cadmium-zinc quantum dots

[0075] Take 4mL of PDI mother solution in a 10mL vial, add 1mL of ethanol solvent (second solvent), and heat it on a hot plate at 65°C. When the system reaches saturation and the PDI monomer is about to self-assemble, the solvent in the vial has evaporated to 1mL. Remove the hot plate and assemble for one hour before adding 100μL of oily sulfur cadmium zinc quantum dot solution. Slowly cool at 25°C to ensure that PDI and quantum dots can be stably self-assembled while polymerizing in situ. After 5 hours of self-assembly, centrifuge and store the resulting assembly in a certain amount of ethanol solvent for quenching to terminate its supramolecular polymerization reaction.

[0076] evaluate:

[0077] (1) Degradation experiment

[0078] The samples obtained in Examples 1 to 3 were used to conduct dark adsorption and dehalogenation tests and photocatalytic reaction activity tests on the organic phase decabromodiphenyl ether substrate solution.

[0079] The dark adsorption and dehalogenation test steps of the sample on the organic phase decabromodiphenyl ether substrate solution are as follows:

[0080] 1. Take 9.59 mg of decabromodiphenyl ether and dissolve it in 10 mL of tetrahydrofuran solution (THF). Take 1 mL of the mixed solution and add 9 mL of ethanol and 90 mL of deionized water.

[0081] 2. Prepare three samples, namely pure sulfur cadmium zinc quantum dots, PDI nanorods with supramolecular self-assembly without quantum dots, and PDI nanorods with segmented quantum dot distribution after in-situ composite with quantum dots, while other conditions are the same.

[0082] 3. Take 1 mL of sample solution in a 100 mL vial and add 10 mL of the mixed solution in step 1. Seal the bottle, wrap it with tin foil, stir it thoroughly and allow it to adsorb darkly for 1 hour.

[0083] 4. Use solar cooker to irradiate for 10 seconds to remove halogen.

[0084] The photocatalytic reaction activity test steps are as follows:

[0085] Take 1.5 mL of the test solution after dehalogenation in step 4 above and filter it through a 0.22 μm pinhole filter into a liquid phase injection bottle. Use acetonitrile as the mobile phase at a flow rate of 1 mL min -1 A C18 reverse phase chromatography column was used for separation and analysis, the wavelength of the UV lamp was 325 nm, and all solvents were ultrasonicated for 10 min before use. The debromination rate was detected by ion chromatography.

[0086] The test results show that under 10s of focused sunlight, the debromination results of decabrominated diphenyl ether by the segmented sulfur cadmium zinc quantum dot PDI sample prepared in Example 1 are as follows: Figure 3 shown.

[0087] The experimental results are shown in Table 1. It can be seen from Table 1 that the photocatalytic activity of PDI monomer without quantum dots is low, and the selectivity of pure sulfur cadmium zinc quantum dots for the target product is poor. When the two are compounded in an orderly manner, the obtained catalyst has an improved effect in degrading decabromodiphenyl ether.

[0088] The test results show that under 10s of focused sunlight, the segmented sulfur-cadmium zinc quantum dot PDI sample prepared in Example 2 can debrominate 100% of decabromodiphenyl ether, degrade all decabromodiphenyl ether, and the obtained products are all final product diphenyl ether. However, under the same conditions, the PDI without quantum dots for supramolecular self-assembly debrominates 20%, and cannot completely degrade the substrate. The photocatalytic activity of pure sulfur-cadmium zinc quantum dots is that the substrate can be completely degraded, but the debromination product is not complete, and a low-brominated product is obtained instead of the final product diphenyl ether.

[0089] Table 1

[0090] Debromination rate of decabrominated diphenyl ether Example 1 48.70% Example 2 100% Example 3 70% Supramolecular self-assembly of PDI without quantum dots 20% Pure CdZnS quantum dots Incomplete debromination of products

[0091] (2) Electron microscope image

[0092] like Figure 1 As shown, Figure 1 Shown are the transmission electron microscope images and element mapping images of the high molecular polymer sample prepared in Example 1. Figure 1 It can be seen that the segment with sulfur-cadmium-zinc quantum dots has a more uniform distribution of S, Cd, and Zn elements than the segment without sulfur-cadmium-zinc quantum dots, and the distribution of elements indicates that the quantum dots are in-situ grown inside the perylene diimide nanorods and are uniformly wrapped by perylene diimide on the outside.

[0093] like Figure 2 As shown, Figure 2 (a)-(c) high-resolution transmission electron microscopy and (d)-(g) transmission electron microscopy images of the one-dimensional segmented nano PDI rods in Example 1, Figure 2 It can be seen that the section with sulfur cadmium zinc quantum dots has a larger thickness, indicating that the quantum dots are successfully recombined, while the section without quantum dots is a thin gauze.

[0094] The high molecular polymer with sulfur-cadmium-zinc quantum dots prepared in Comparative Example 1 was tested by transmission electron microscopy:

[0095] The experimental results show that when the segmented PDI assembly time is insufficient, uniform segmentation cannot be formed. Figure 4 shown.

[0096] The high molecular polymers with sulfur-cadmium-zinc quantum dots prepared in Comparative Examples 2, 3, and 4 were tested by transmission electron microscopy:

[0097] The experimental results show that the segmented PDI cannot form uniform segments at 10℃, 20℃ and 40℃, and even the quantum dots cannot be fully composited. Figure 5 shown.

[0098] The high molecular polymer with sulfur-cadmium-zinc quantum dots prepared in Comparative Example 5 was subjected to transmission electron microscopy test: The experimental results show that after the PDI has been partially self-assembled, the addition of sulfur-cadmium-zinc quantum dots cannot form uniform segments, and the quantum dots cannot be compounded inside the PDI nanorods, but are loaded on the surface of the nanorods. The results are as follows Figure 6 shown.

[0099] Conclusion: Figure 3 It can be seen that the polymer with segmented distribution of sulfur-cadmium zinc quantum dots prepared in the embodiment is used to degrade decabromodiphenyl ether, and a low-bromine product can be obtained, which is practical; from comparative example 1, the assembly time is changed, and uniform segmentation cannot be formed; comparative example 2 is slowly cooled at 10°C, 20°C and 40°C respectively, and uniform segmentation cannot be formed, and even the quantum dots cannot be completely compounded; comparative example 3 takes off the hot stage and assembles for one hour and then adds a certain amount of oily sulfur-cadmium zinc quantum dot solution, which cannot form uniform segmentation, and the quantum dots cannot be compounded inside the PDI nanorods, but are loaded on the surface of the nanorods. In summary, the polymer with segmented distribution of sulfur-cadmium zinc quantum dots prepared by the present invention has the advantages of high strength, not easy to be destroyed, high temperature resistance, little environmental impact, more stable when illuminated, high controllability, environmentally friendly, no pollution to the environment, relatively simple preparation process, convenient operation, and significant degradation effect on decabromodiphenyl ether.

[0100] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0101] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots, characterized in that: The following steps are involved: S1: mixing perylenetetracarboxylic dianhydride, dodecylamine and imidazole to react to obtain a perylene diimide derivative; S2: mixing sulfur powder, octadecene, cadmium oxide, zinc acetate and oleylamine to react to obtain sulfur-cadmium-zinc quantum dots; S3: assembling and compounding the perylene diimide derivative and the cadmium zinc sulfur quantum dots to obtain a high molecular polymer in which the cadmium zinc sulfur quantum dots are distributed in sections; In step S3, the temperature of the assembly is 25-35°C; In step S3, the assembly time is greater than or equal to 5 hours.

2. The method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots according to claim 1, characterized in that: In step S3, the assembling and compounding of the perylene diimide derivative and the cadmium zinc sulfur quantum dots comprises dissolving the perylene diimide derivative in a first solvent, wherein the ratio of the perylene diimide derivative to the first solvent is (5-15) mg / 100 ml.

3. The method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots according to claim 2, characterized in that: In step S3, the assembly and compounding comprises adding a second solvent to the perylene diimide derivative dissolved in the first solvent and heating and evaporating the solvent, and when the system reaches saturation, simultaneously adding the sulfur cadmium zinc quantum dots for assembly and compounding.

4. The method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots according to claim 3, characterized in that: When the volume of the perylene diimide derivative to which the second solvent is added is reduced by 4 / 5 by heating and evaporation, the sulfur cadmium zinc quantum dots are added.

5. The method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots according to claim 1, characterized in that: The preparation of the perylene diimide derivative comprises the following steps: mixing perylene tetracarboxylic dianhydride, dodecylamine and imidazole and calcining at 130° C. to obtain a solid; The solid is dispersed and centrifugally dried to obtain the perylene diimide derivative.

6. The method for preparing a high molecular polymer with segmented distribution of sulfur-cadmium-zinc quantum dots according to claim 1, characterized in that: The preparation of the sulfur-cadmium-zinc quantum dots comprises: heating and dissolving sulfur powder and octadecene to obtain a precursor; Mixing cadmium oxide, zinc acetate, octadecene and oleylamine, heating and dissolving them, and then mixing them into the precursor to react to obtain a reactant; The reactants are centrifuged to remove impurities and then dispersed in a first solvent at low temperature.

7. A polymer with segmented distribution of zinc cadmium sulfur quantum dots obtained by the method for preparing a polymer with segmented distribution of zinc cadmium sulfur quantum dots according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Bay-substituted perylene diimide derivative and preparation method thereof

    CN117486879A

  • Process cartridge and electrophotographic apparatus

    JP2006119518A